Logam Berat Timbal (Pb) dan Kadmium (Cd) pada Beberapa Jenis Ikan Demersal di Perairan Teluk Manado, Sulawesi Utara - Chairil Anwar; Djuhria Wonggo; Eunike Mongi (Media Teknologi Hasil Perikanan, 2022)
The purpose of this study was to determine the levels of heavy metal Lead (Pb) and heavy metal Cadmium (Cd) in several types of demersal fish in the waters of Manado Bay. The samples used were 6 types of demersal fish commonly found in the bay of Manado, namely Sillago sihama, Lethrinus obsoletus, Garres filamenysuso, Polydactylus plabejus, Lutjanus rusellii and Mugil cephalus. Analysis of heavy metal content using the Atomic Absorption Spectro-photometry (AAS) method. The levels of heavy metals in fish samples were compared with the quality standards set by the Consumption Safe Limit (BSN) SNI 7387:2009. The results showed that the levels of Lead (Pb) were <0.08 mg/kg and Cadmium (Cd) were <0.01 mg/kg for each sample of demersal fish. Keyword:        Pb, Cd, Heavy Metals, Demersal fish, Manado Bay.